African American Vernacular English An analysis of Kevin Hart’s humor in the movie ‘What Now?’ and the perception of English speakers in the United States about AAVE - Serrano Egas, Sami Violeta (2021)
This research project is mainly a descriptive-synchronic analysis of African American Vernacular English based on Kevin Hart's comedic repertoire, specifically two of his standup comedy shows "What Now?" and "Let Me Explain". Additionally, this project focuses on portraying the opinion of different speech and social communities have not only about this specific dialect but also about English in general.